Effects of continuous light and light intensity on the growth performance and gonadal development of Nile tilapia - Carlos Cristian Martínez-Chávez; Pamela Navarrete-Ramírez; Deborah Victoria Parke; Herve Migaud (Revista Brasileira de Zootecnia, 2021)
ABSTRACT Continuous illumination has been known to exert positive effects by stimulating growth and delaying unwanted maturation in seasonal-temperate farmed fish species like salmonids. However, in tropical fish like Nile tilapia ( Oreochromis niloticus ), some studies exist showing inconsistent results and even fewer data is available regarding the effects of light intensity. To clarify some of the inconsistent results in literature and evaluate the effect of different light intensity levels on growth and sexual maturation in Nile tilapia ( Oreochromis niloticus ), we reared twenty days post-hatch Nile tilapia larvae under continuous illumination at three different light intensities and compared against a control photoperiod (12L:12D) up to 118 days post-hatch. A total of 600 fry were used using 75 fry per experimental unit in a previously tested experimental aquarium setup. Fish exposed to high and medium intensity continuous illumination treatments were significantly heavier (13-20%) and longer (6-8%) than fish exposed to the control photoperiod. Importantly, however, the degree of growth enhancement did not vary significantly according to the light intensity used. Feed intake was also higher in all continuous illumination treatments than in the control photoperiod, suggesting that growth benefits might be due to an increase in feed intake, which is not affected by the light intensities used. Gonadal development on the other hand, presented differences between sexes with a delay in spermatogenesis, while an advancement towards ovarian maturation occurred compared with the control fish. These results suggest that continuous illumination can influence both growth and gonadal development in Nile tilapia with no apparent differences between the light intensities tested in this study.